(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The presence of atopic genesis of allergic pathology in children is confirmed by the detection of overproduction of total IgE, specific IgE antibodies, and positive skin tests with allergens. The group of patients classified as atopic, is based on identifying a family predisposition to allergic reactions and diseases and obtaining evidence of the leading role of the IgE-mediated mechanism in their development.